Establishment of a Mutant Library for Infection Cushion Development and Identification of a Key Regulatory Gene in Botrytis cinerea - Maoyao Tang; Kexin Wang; Pan Zhang; Jie Hou; Xiaoqian Yu; Hongfu Wang; Yangyizhou Wang; Guihua Li (Journal of Fungi)
Botrytis cinerea, the grey mould fungus affecting over 1400 plant species, employs infection cushion (IC), a branched and claw-like structure formed by mycelia, as a critical strategy to breach host surface barriers. However, the molecular mechanisms underlying IC formation remain largely unexplored. In this study, we utilized a forward genetics approach to establish a large T-DNA tagged population of B. cinerea, which contained 14,000 transformants. Through phenotype screening, we identified 161 mutants with defects in IC development. Detailed analyses revealed that these mutants exhibited various degrees of impairment in IC formation, ranging from complete failure to form ICs to a reduction in the number and maturity of ICs. Further genetic analysis of one of the mutants led to the identification of EXO70, a gene encoding a component of the exocyst complex, as a key regulatory factor in IC development. Mutants with deletion of EXO70 failed to form ICs, confirming its crucial role in the process. The mutant library reported here provides a rich resource for further large-scale identification of genes involved in IC development. Our findings provide valuable insights into the genetic and molecular basis of IC formation and offer new targets for controlling B. cinerea pathogenicity.